Distribution of patients with fixed orthodontic treatment based on age, gender, education level, and occupation - Maysa, Dara; Malik, Isnaniah; Zenab, Yuliawati (Padjadjaran Journal of Dentistry, 2015)
Introduction: Fixed orthodontic is one of the option to correct malocclusions. Factors of age, gender, educational background and occupation of an individual can affect the understanding and concern regarding oral health. It also deter-mines a person’s attitude in choosing the right treatment. This study was aimed to determine the distribution of patient with fixed orthodontic treatment based on age, gender, education level, and occupation in Universitas Padjadjaran Dental Hospital. Methods: This study was conducted with a descriptive method by collecting all the data of the patient with fixed orthodontic treatment from the medical record in Universitas Padjadjaran Dental Hospital during the 2009-2011 period. Results: The results showed that fixed orthodontic treatment was majority used by 71.65% adults, 79.53% females, 50.39% patients in the level of education of high school, and 53.54% by the university student. Conclusion: Fixed orthodontic treatment is used more by adults, females, high school graduated, and patient with occupation as a university student.